A Supramolecular Strategy to Leverage the Liquid‐Phase Exfoliation of Graphene in the Presence of Surfactants: Unraveling the Role of the Length of Fatty Acids. Issue 14 (15th December 2014) - Haar, Sébastien; Ciesielski, Artur; Clough, Joseph; Yang, Huafeng; Mazzaro, Raffaello; Richard, Fanny; Conti, Simone; Merstorf, Nicolas; Cecchini, Marco; Morandi, Vittorio; Casiraghi, Cinzia; Samorì, Paolo
<x xml:space="preserve">Abstract</x> Achieving the full control over the production as well as processability of high‐quality graphene represents a major challenge with potential interest in the field of fabrication of multifunctional devices. The outstanding effort dedicated to tackle this challenge in the last decade revealed that certain organic molecules are capable of leveraging the exfoliation of graphite with different efficiencies. Here, a fundamental understanding on a straightforward supramolecular approach for producing homogenous dispersions of unfunctionalized and non‐oxidized graphene nanosheets in four different solvents is attained, namely N‐methyl‐2‐pyrrolidinone, N, N‐dimethylformamide, ortho‐dichlorobenzene, and 1, 2, 4‐trichlorobenzene. In particular, a comparative study on the liquid‐phase exfoliation of graphene in the presence of linear alkanes of different lengths terminated by a carboxylic‐acid head group is performed. These molecules act as graphene dispersion‐stabilizing agents during the exfoliation process. The efficiency of the exfoliation in terms of concentration of exfoliated graphene is found to be proportional to the length of the employed fatty acid. Importantly, a high percentage of single‐layer graphene flakes is revealed by high‐resolution transmission electron microscopy and Raman spectroscopy analyses. A simple yet effective thermodynamic model is developed to interpret the chain‐length dependence of the exfoliation yield. This approach relying on the synergistic effect of a ad‐hoc solvent and molecules to promote the exfoliation of graphene in liquid media represents a promising and modular strategy towards the rational design of improved dispersion‐stabilizing agents.